Pre-Service Biology Teachers’ Pedagogical Skills and Usability of Mobile Technology for Instructional Delivery During Teaching Practice - Bolanle Tawakalt-Anu Abdulazeez; Hameed Olalekan Bolaji; Adebayo Zakariyau Bello (Universitas Negeri Semarang, 2024)
The ease of using mobile technology for teaching is hindered by deficiencies in teacher training programs. This study aims to address this issue and explore solutions for improving the use of mobile technology in teaching in Nigeria, particularly focusing on how pre-service science teachers can acquire pedagogical skills through mobile technology during teaching practice.Using a descriptive research method of the survey type, the study addresses five research questions and tests two research hypotheses at a significance level of 0.05. The population comprises science education students in public and private institutions in Ilorin, with samples drawn randomly from three colleges of education in different local government areas. A total of 285 respondents participated, providing data through a researcher-designed questionnaire titled